2022
DOI: 10.35194/jm.v12i2.2732
|View full text |Cite
|
Sign up to set email alerts
|

Description of Physical Activity Level of Medical Faculty Students of Pasundan University in The New Normal Era

Abstract: Physical activity has various benefits, especially for health because it can prevent degenerative diseases and other non-communicable diseases. The level of physical activity is also in line with the level of physical fitness and this is very important for students to be able to carry out good learning activities and ultimately affect the learning outcomes and achievements achieved. The existence of reports of cases of new sub-variant COVID infection indicates that the COVID-19 pandemic is not over and demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Female medical students are vulnerable due to their busy academic schedules, resulting in the less time for physical activity (Al-Asousi & El-Sabban, 2016). Research results showed that the majority of female medical students had low physical activity levels (Annamayra et al, 2022). Physical activity is actually one stimuli of the anabolic hormones, namely growth hormone (GH), insulin-like growth factor 1 (IGF-1), testosterone, and estrogen (Distefano & Goodpaster, 2018;Gharahdaghi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Female medical students are vulnerable due to their busy academic schedules, resulting in the less time for physical activity (Al-Asousi & El-Sabban, 2016). Research results showed that the majority of female medical students had low physical activity levels (Annamayra et al, 2022). Physical activity is actually one stimuli of the anabolic hormones, namely growth hormone (GH), insulin-like growth factor 1 (IGF-1), testosterone, and estrogen (Distefano & Goodpaster, 2018;Gharahdaghi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific studies state that sport is more than just physical activity and games, but also has economic and character values that can unite individuals from different social classes, ages, genders and countries. Physical activity also contains some benefits for physical and mental health, such as improving brain health, chronic diseases, and improving physical and mental health to reduce medical costs and prevent various diseases (Annamayra et al, 2022). Moreover, excess weight due to a lack of physical activity will damage students' motor skills (Priyohutomo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%